(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article is devoted to the study of the role, global distribution and status of the English language in the modern world. The authors study the factors that contribute to the spread of the English language and the history of its development. Borrowing is an important factor in the development and change of the lexical system of language. The borrowed words were divided into classification. Now the world is in transition, and English takes on new forms. Language reflects patterns of contrast with other languages and the changing needs of people in communication. The popularity of English as a language of communication will continue to exert pressure on global uniformity. This can lead to lower standards, language changes and the loss of linguistic diversity. English will become a tool that opens the windows to the world, opens the door for opportunities and expands our minds with new ideas. The types of borrowings in some European countries have been examined and analyzed. We have come to a general conclusion about the relevance of studying the borrowing words.